TINGGI IBU SEBAGAI DETERMINAN STUNTING PADA BALITA DI KALIMANTAN TIMUR - Nino Adib Chifdillah; Kurniati Dwi Utami; Ratnawati Ratnawati (MMJ (Mahakam Midwifery Journal), 2019)
Abstract Indonesia is country with the fourth highest prevalence of stunting among under 5-years old children in the world and the second highest of that in Southern Asia. Maternal factors is so important because they become the main determinants and source of stunting prevention. This research aimed to analyze the sociodemography, parenting and food intake of mother as determinant of stunting. The research was cross sectional study with 97 under 5-years old children in chosen Posyandu. Measurement of body height of mother and under 5-years old children who had stood by microtoise. Meanwhile measurement of under 5-years old children who had not stood by length board. There were three variables related to stunting among under 5-years old children. They are parity (p-value=0,017), the height of mother (p-value=0,009) and the level of income (p-value=0,036). The most dominant variable related to stunting among under 5-years old children was the height of mother (OR=3,1). Determinants of stunting among under 5-years old children were parity, height of mother and the level of income. Keywords: stunting, under 5-years old children, height of mother Abstrak Indonesia adalah negara dengan prevalensi balita stunting terbesar keempat di dunia dan tertinggi kedua di wilayah Asia Tenggara. Faktor ibu layak menjadi perhatian karena menjadi determinan dan sumber utama pencegahan stunting. Penelitian ini bertujuan untuk menganalisis faktor sosiodemografi ibu, pola asuh dan asupan makanan sebagai determinan stunting. Desain penelitian ini adalah cross sectional dengan jumlah sampel 97 balita yang terdaftar di Posyandu. Pengukuran tinggi badan ibu dan balita yang sudah bisa berdiri menggunakan microtoise. Sementara pengukuran panjang badan balita yang belum bisa berdiri menggunakan length board. Terdapat tiga variabel yang berhubungan dengan kejadian stunting pada balita. Ketiga variabel tersebut adalah paritas (p-value=0,017), tinggi badan ibu (p-value=0,009) dan tingkat pendapatan (p-value=0,036). Variabel yang paling dominan berhubungan dengan kejadian stunting pada balita adalah tinggi badan ibu (OR=3,1). Determinan stunting balita antara lain faktor paritas, tinggi badan ibu dan tingkat pendapatanAbstrak dalam Bahasa Indonesia. Kata Kunci: stunting, balita, tinggi badan ibu